Immunotherapeutic Effects of Different Doses of Mycobacterium tuberculosis ag85a/b DNA Vaccine Delivered by Electroporation - Liang, Yan; Cui, Lei; Xiao, Li; Liu, Xiao; Yang, Yourong; Ling, Yanbo; Wang, Tong; Wang, Lan; Wang, Jie; Wu, Xueqiong (Frontiers in Immunology, 2022)
Background Tuberculosis (TB) is a major global public health problem. New treatment methods on TB are urgently demanded. Methods Ninety-six female BALB/c mice were challenged with 2×104 colony-forming units (CFUs) of MTB H37Rv through tail vein injection, then was treated with 10μg, 50μg, 100μg, and 200μg of Mycobacterium tuberculosis (MTB) ag85a/b chimeric DNA vaccine delivered by intramuscular injection (IM) and electroporation (EP), respectively. The immunotherapeutic effects were evaluated immunologically, bacteriologically, and pathologically. Results Compared with the phosphate-buffered saline (PBS) group, the CD4+IFN-γ+ T cells% in whole blood from 200 µg DNA IM group and four DNA EP groups increased significantly (P<0.05), CD8+IFN-γ+ T cells% (in 200 μg DNA EP group), CD4+IL-4+ T cells% (50 μg DNA IM group) and CD8+IL-4+ T cells% (50 μg and 100 μg DNA IM group, 100 μg and 200 μg DNA EP group) increased significantly only in a few DNA groups (P< 0.05). The CD4+CD25+ Treg cells% decreased significantly in all DNA vaccine groups (P<0.01). Except for the 10 μg DNA IM group, the lung and spleen colony-forming units (CFUs) of the other seven DNA immunization groups decreased significantly (P<0.001, P<0.01), especially the 100 μg DNA IM group and 50 μg DNA EP group significantly reduced the pulmonary bacterial loads and lung lesions than the other DNA groups. Conclusions An MTB ag85a/b chimeric DNA vaccine could induce Th1-type cellular immune reactions. DNA immunization by EP could improve the immunogenicity of the low-dose DNA vaccine, reduce DNA dose, and produce good immunotherapeutic effects on the mouse TB model, to provide the basis for the future human clinical trial of MTB ag85a/b chimeric DNA vaccine.